Assessment of Prevalence and Gender Distribution of Congenitally Missing Maxillary Lateral Incisors - M, APARNA.; B, NIVETHIGAA; V, RAKSHAGAN (The journal of contemporary issues in business and government, 2021)
Tooth agenesis refers to the developmental failure of a tooth and could be classified into anodontia or partial anodontia. It is more frequently observed on the permanent dentition with more frequency for the upper arch than in lower arch. Many studies had evaluated the prevalence of congenitally missing lateral incisors among various populations previously. The main aim of the study is to assess the prevalence and gender distribution of congenitally missing maxillary lateral incisors among a sample of 10000 patients in an institutional set-up. Dental records and radiographs were retrospectively examined for the presence of missing maxillary lateral incisors. Data was retrieved from the dental case records of Saveetha Dental College, Chennai. Details like age, gender, absence of missing lateral incisors may be unilateral (or) bilateral were retrieved from the source and analysed. Lesser prevalence rate of missing maxillary lateral incisors among the examined population (n=10,000) was found.